ANALISIS KETIMPANGAN PEMBANGUNAN WILAYAH DAN STRATEGI PERENCANAAN PEMBANGUNAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Nabila Maulidya; Pasya Isna Novita; Zahroul Lailatur Rohmah; Teguh Hadi Priyono (Relawan Jurnal Indonesia, 2026)
This study aims to analyse regional development disparities and formulate development planning strategies in the Special Region of Yogyakarta. A mixed-methods approach was employed, comprising a quantitative analysis using Klassen’s typology and a qualitative analysis using SWOT analysis. The data used were secondary data sourced from the Central Statistics Agency and related institutions for the period 2021–2025. The research findings indicate that there are development disparities between districts and cities in the Special Region of Yogyakarta. The City of Yogyakarta falls into the category of a developed and rapidly growing region; Sleman District is a developed region but under pressure; Gunungkidul and Kulon Progo Districts are rapidly developing regions; and Bantul District is a relatively underdeveloped region. These disparities are influenced by the concentration of economic activities, uneven distribution of investment, and differences in economic structure between regions. Based on a SWOT analysis, policies that can be implemented to reduce these disparities include strengthening development based on regional equity, economic diversification based on the local economy, and strengthening fiscal capacity and regional governance. Consequently, development policies are required that focus not only on economic growth but also on the equitable distribution of development outcomes across regions.